2015
DOI: 10.1080/15332691.2014.953651
|View full text |Cite
|
Sign up to set email alerts
|

The Pleasures and Perils of Technology in Intimate Relationships

Abstract: Technologies have rapidly become pervasive parts of people's lives and relationships. Within intimate couple relationships, partners may use technologies for many functions, including communicating, sharing affection, planning, and learning about one another. There is growing recognition that these functions can create both positive and negative outcomes for couples. The purpose of this study was to conduct an in-depth examination of the potential positive and negative impacts of technology for intimate couple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 28 publications
0
25
0
Order By: Relevance
“…Given this situation, the idea for this Special Issue developed during the follow-up to a symposium organized by the guest editors at the European Family Therapy Association Murray and Campbell 2015;Morgan et al 2016;Vossler 2016). Besides, we have to consider the impact of ICTs on psychological development and individuation processes since early stages of life (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Given this situation, the idea for this Special Issue developed during the follow-up to a symposium organized by the guest editors at the European Family Therapy Association Murray and Campbell 2015;Morgan et al 2016;Vossler 2016). Besides, we have to consider the impact of ICTs on psychological development and individuation processes since early stages of life (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…32 Nonetheless, not all online interactions are detrimental to romantic relationships. 33,34 For example, Grov and colleagues 35 showed that moderate or light amounts of online sexual activities can yield relationship benefits, including increases in the quality and frequency of sex, and greater intimacy with the primary partner. This seems to depend on the agreements conveyed in the relationship and on what role technologymediated behaviors play in the relationship.…”
mentioning
confidence: 99%
“…A growing reliance on smartphone technologies for social interactions has triggered an onslaught of research into the social and mental health implications for individuals (Liu et al, 2019). Meanwhile, the empirical literature on mobile communication in romantic relationships remains sparse (Murray & Campbell, 2015;Norton et al, 2018). Although LDR couples have been finding ways to cultivate satisfying relationships long before the dawn of smartphones, results from the current study provide evidence for a uniquely beneficial role of frequent and responsive text messaging for people in LDRs (but not GCRs).…”
Section: Discussionmentioning
confidence: 72%